Liverwort diversity in Polylepis pauta forests of Ecuador under different climatic conditions. Issue 1 (1st January 2020) - Gradstein, S. Robbert; León-Yánez, Susana
ABSTRACT: Polylepis: forests are the world's highest forests in terms of elevation and host a unique biodiversity of plants and animals. Unfortunately, these forests are rapidly disappearing due to human impact and are one of the most threatened ecosystems of South America. This paper deals with liverwort diversity in Polylepis forests of Ecuador. Liverworts are very diverse in tropical forests and are sensitive indicators of changes in humidity conditions. By comparing species richness, species composition and composition of functional groups of liverworts in dry and humid Polylepis forest, we explore how liverwort diversity of Polylepis forests is affected by climatic conditions differing in humidity. We inventoried liverwort diversity in Polylepis pauta forest of Lagunas de Mojanda reserve characterized by a relatively dry climate and in the páramo of Papallacta with a humid climate. In each site, we sampled liverworts on 10 P. pauta trees and surrounding soil. Species richness was highest in the humid forest and species composition in the two sites differed significantly. The two sites also had very different patterns of functional groups, with smooth mats dominating the liverwort flora of Mojanda while rough mats prevailed at Papallacta. This underscores the importance of bryophyte life forms as climate indicators in tropical forests. A phytogeographic comparison of the two sites showed a higher number of northern Andean taxa in the humid forest. The greater representation of species with restricted ranges in humid Polylepis forest shows the importance of these forests for conservation.